Doing Business 2014 Economy Profile : Romania - World Bank; International Finance Corporation (World Bank Group, Washington, DC, 2014)
This economy profile presents the Doing Business indicators for Romania. In a series of annual reports, Doing Business assesses regulations affecting domestic firms in 189 economies and ranks the economies in 10 areas of business regulation, such as starting a business, resolving insolvency and trading across borders. This year's report data cover regulations measured from June 2012 through May 2013. The report is the 11th edition of the Doing Business series.